Mycorrhizal diversity of an endemic terrestrial orchid - Sharma, Jyotsna (Universidad de Costa Rica, 2015)
Mycorrhizal associations of the Orchidaceae - the largest and most diverse angiosperm family with an estimated number of taxa ranging between 17,000 and 35,000 – are highly complex. Plant-fungus inter- actions in this family can range from obligate- or fac- ultative mycotrophy, mutualism, to minimal depen- dence on fungi in adulthood (Smith & Read 1997, Sivasithamparam et al. 2002, Taylor et al. 2002, Cameron et al. 2006).